Analisis Kinerja Sosial dan Keuangan Lembaga Keuangan Mikro Puap Di Desa Pandau Jaya Kecamatan Siak Hulu Kabupaten Kampar - Martua Siahaan; Ahmad Rifai; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Gapoktan Tani Jaya that located in the Pandau Jaya Village of Kampar District is one of the beneficiaries of Rural Agribusiness Development ( PUAP ) which has been running for 5 years . Until now , there has been no discourse to improve PUAP institutions into MFI - A. An MFI - A should have social performance in its outreach and financial performance with good level financial position (Arsyad, 2008). Based on the explanation , aim of this research are: to analyze the social performance, analyzing the financial performance of institutions and policy implications the results of the analysis of social performance and financial performance of the institution. The data used are secondary data derived from the financial statements and progress reports of institution membership in 2009 until 2012 and the primary data is interviews to PPL and agency managers. Outreach of institutional customers is fluctuated because there are non-active members at a later stage. Staff outreach is considered good because it can meet all the needs of members. Loan outreach also fluctuate because there are non-active members and the existence of arrears in 2011 and 2012. Savings range is considered good because a lot of members who do voluntary savings each year. Sales of fertilizer also has a positive effect on the development of the institution's revenues. Liquidity and solvency ratio has decreased every year but the value of the ratio is still in a liquid state and solvable. Profitability and activity ratio is considered good although profits are quite small but positive effect on institutions and organizations are also able to streamline the activities of financial resources. The policy implications of the institutions should increase the number of active borrowers and reduce operational costs , and increase profits from the activity of the institution. Keywords: Gapoktan, Social Performance, Financial Performance, PUAP.